Dynamic CT perfusion imaging for type 2 endoleak assessment after endograft placement. (June 2020) - Charalambous, Stavros; Kontopodis, Nikolaos; Perisinakis, Kostas; Papadakis, Antonios E.; Kehagias, Elias; Galanakis, Nikolaos; Matthaiou, Nikolas; Maris, Thomas G.; Ioannou, Christos V.; Tsetis, Dimitrios
Abstract: Endovascular repair of abdominal aortic aneurysm is a widely performed treatment method due to its minimal invasiveness, reduced need for intensive care unit (ICU), shorter hospitalization and lower 30-day morbidity and mortality compared to open surgery. Endoleak is the drawback of this procedure and is considered the main culprit for re-interventions due to the risk of late aneurysm sac growth and rupture. Type 2 endoleak (T2EL) is the most common type of endoleak which is also the most controversial regarding its management. The aim of this paper is to investigate the potential of dynamic contrast-enhanced CT for the assessment of T2EL after endovascular aneurysm repair using qualitative and quantitative image analysis of the aneurysmal sac.